ANALISIS TERHADAP DETERMINAN SPREAD SUKU BUNGA BANK UMUM DI INDONESIA PERIODE 2009-2013. - Sari, Linda Ratna (Jurnal Ekonomi Pembangunan, 2015)
This study was aimed to know the effect of dependent variable, spread of public bank rate in Indonesia period 2009-2013.Multiple linear regressions with model of least quadrat estimation were used as analysis tool. In the model equation, spread rate of interest (interest rates on loans and interest rates on savings) was a dependent variable, and then the independent variable was BI rate, ROA, NPL, and SIBOR.The result of this current study showed that BI rate and ROA had a negative effect and significant on spread rate of interest, whereas NPL and SIBOR had a positive effect and significant on spread rate of interest. Simultaneously, BI rate, ROA, NPL, SIBOR influence the spread rate of interest. Meanwhile, trial on classic assumption showed that all regressions had pulled through from classic assumption (autocorrelation, heterocedasticity, multicollinearity). Coefficient determination (R2) of regression interest rate spread was 0,708181 or 70.82%. it showed that independent variable consist of BI rate, ROA, NPL, and SIBOR clarified the changing of dependent variable interest rate spread as big as 70.82%, whereas the remaining 0.29% was clarified by other variable that is not included in estimation model.